Decentralised planning for population stabilisation - Ranjan Alok; Dass Ishwar (Bhopal Population Resource Centre, 2005)
It provides a systematic exposition of the process of decentralized community needs based on planning for population stabilization at the district level for the implementation of Madhya Pradesh Population Policy 2000 in the district Chhatarpur as part of
Keywords: India; Madhya pradesh; Population policy